Simone de Beauvoir : a humanist thinker - Pettersen, Tove, 1962-; Bjørsnøs, Annlaug.; Simons, Margaret A. (Value Inquiry Book Series, 2015)
This collection of humanist readings of Simone de Beauvoir's work is a novel contribution to contemporary research on Beauvoir, and a defense of the importance of the humanities. It demonstrates the significance and value of humanistic research through the work of Beauvoir, and argues that the reception and influence of her works demonstrate the transformative potential of humanistic research. Organized around three topics, each chapter ascertains Beauvoir's relation to the humanities and the humanist tradition. The first group focuses on Beauvoir's interdisciplinary methodology and critical thinking, the second on her ethics of freedom and the construction of values. The last section explores how Beauvoir uses literature as a laboratory for developing her ideas on human interaction. The chapters can be studied as independent essays, or read together as a whole. Simone de Beauvoir-A Humanist Thinker reveals new and previously unexplored dimensions of Beauvoir's work by exposing her as a significant and inspiring humanist thinker. This volume attests that Beauvoir's works continue to offer conceptual tools and insights enabling readers to critically analyze their own situation. In today's world, where religious fanaticism and totalitarian ideologies are gaining ground, humanist values and humanistic research are more important than ever.